Marzano's instructional strategies: fostering information analysis and processing skills of plant anatomy in teacher education - Anna Fitri Hindriana; Behailu Merdekios Gello; Ina Setiawati; Handayani Handayani; Alin Rizki Pratami (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2025)
This study proposes a design for a Plant Anatomy course by adapting Marzano's instructional framework to develop students’ information analysis and processing skills. The focus of the Plant Anatomy course is determined because it requires complex cognitive processing to integrate knowledge about plant tissue structure with changes in plant structure based on adaptation strategies in their habitat. This study employs a quantitative method, utilising information analysis ability tests and process skills tests as its instruments. The data were analysed descriptively using an assessment rubric. The design is then tested on 106 undergraduate students in Biology Education taking the Plant Anatomy course during data collection at a university in West Java, Indonesia. The results showed that the Marzano-based plant anatomy course design could facilitate students' information analysis and processing skills due to a conducive learning environment, the utilisation of prior knowledge, the development of thinking potential, the delivery of meaningful information, contextual learning, and cooperative learning. This study further proposes using this design when studying materials with a high concept interconnection.